Clinical characteristics and outcomes of HIV‐infected children diagnosed with kaposi sarcoma in malawi and botswana. Issue 8 (11th March 2013) - Cox, Carrie M.; El‐Mallawany, Nader Kim; Kabue, Mark; Kovarik, Carrie; Schutze, Gordon E.; Kazembe, Peter N.; Mehta, Parth S.
Abstract Background Kaposi sarcoma (KS) is the most common HIV‐associated malignancy in sub‐Saharan Africa. The presentation and outcomes of pediatric KS are not well understood. Procedure We performed a retrospective cohort analysis of 81 HIV‐infected children with KS at the Baylor Children's Clinical Centres of Excellence in Malawi and Botswana from March 2003 to October 2009. Results Eighty‐one children with KS were identified whose median age was 8.0 (inter‐quartile range 5.1–11.3) years. KS lesions were presented primarily on the skin (83%), lymph nodes (52%), and oral mucosa (41%). Occasionally disease was limited to the lymph nodes only (10%). Severe immunosuppression (70%), anemia (29%), and thrombocytopenia (17%) were common laboratory findings. Highly active antiretroviral therapy (HAART) was administered to 94% of children, including 77% who received HAART plus chemotherapy. KS immune reconstitution inflammatory syndrome (IRIS) occurred in 22%. Disease status 12 months after KS diagnosis was determined for 69 children: 43% were alive and 57% had died. Severe immunosuppression was independently associated with mortality in multivariate analysis (OR = 4.3; 95% CI 1.3–14.6; P = 0.02). Conclusion KS occurs in a significant number of HIV infected children in sub‐Saharan Africa. Pediatric KS is distinct from KS in adults. Lymph node involvement was a common manifestation of KS in children, and severe immunosuppression was associated with the highest mortality risk. Though overall mortality was high in children with KS, patients did achieve clinical remission in settings with limited diagnostic and therapeutic resources. Pediatr Blood Cancer 2013;60:1274–1280. © 2013 Wiley Periodicals, Inc.